Gambaran Sistem Rujukan Pasien di Puskesmas Alalak Selatan Banjarmasin: Description of the Patient Referral System at the Alalak Selatan Banjarmasin Community Health Center - Muhammad Rashif Anshari; Restiana Utami; Annisa Fajarini; Robi'atul Adawiyah; Cindy Natasya (UPPM Politeknik Unggulan Kalimantan, 2025)
Community health centers are primary health care facilities that play an important role in the implementation of patient referral systems as part of tiered health care services. A good referral system is necessary to ensure continuity of service, accuracy of patient treatment, and completeness of referral administration. This study aims to describe the patient referral system implemented at the Alalak Selatan Community Health Center in Banjarmasin. The research method used was descriptive research with an observational approach, through direct observation and data collection during the internship. The results showed that the patient referral process was carried out by general practitioners through the e-Puskesmas application, both for emergency and non-emergency referrals. The referral system has been integrated electronically, facilitating patient data recording and the completeness of referral administration. However, there is still a need for a more systematic understanding of the referral process to support the smooth running of services. The conclusion of this study is that the patient referral system at the Alalak Selatan Community Health Center in Banjarmasin is operating electronically and is integrated, and plays a role in supporting the smooth running of patient referral services.